Removal of Nutrients From Anaerobically Digested Swine Wastewater Using an Intermittent Cycle Extended Aeration System - Dan, Nguyen Hong; Rene, Eldon R.; Le Luu, Tran (Frontiers in Microbiology, 2020)
The swine wastewater contains high concentrations of organic compounds, nutrients (nitrogen and phosphorus), heavy metal, residual antibiotics that bring a negative impact on the water environment. In this work, for the first time, the anaerobically digested swine wastewater was treated using an intermittent cycle extended aeration system (ICEAS). Effect of some operation parameters such as cycle time, organic loading rate, C/N ratio, aeration/mixing ratio to the pollutant removal efficiencies of ICEAS were studied and compared with conventional sequencing batch reactor (SBR). The results show that the optimal cycle time was 6 h, the organic loading rate was 0.86 kgCOD/m3.d, the C/N ratio was 2.49-2.82, and the aeration/mixing ratio was 1.62. The pH was steady in the range of 6.0 - 8.0. The best chemical oxygen demand (COD), biochemical oxygen demand (BOD5), total organic carbon (TOC), total nitrogen (TN) and total phosphorus (TP) removal efficiencies were 93.11%, 98.77%, 90.15%, 90.16% and 95.21%. The pollutant removal efficiencies of ICEAS are higher than conventional SBR technology, especially nitrogen and phosphorous parameters. ICEAS is a promising technology to remove organic contaminants and nutrients in anaerobically digested swine wastewater to match with the Vietnamese discharge standard for swine wastewater effluent QCVN 62-MT:2016/BTNMT.